Romanticizing Conversion Narratives: Women, Change, and Female Agency in Twilight and Joseph and Aseneth - Howard, Melanie A. (Journal of religion and popular culture, 2019)
Stephenie Meyer's Twilight series recounts the conversion of the female protagonist, Bella, from human to vampire. This conversion is reminiscent of an earlier tale of conversion in the Second Temple apocryphal account Joseph and Aseneth. This article argues that both works can be understood as romanticized conversion narratives that are differentiated by the degree to which they endow their female protagonists with agency and autonomy. While both tales include common elements (for example, a similar narrative arc and gendered elements of the conversion process), there is a notable difference in the level of the woman's agency during her conversion.